Multimorbidity matters in low and middle-income countries - Ana Basto-Abreu; Tonatiuh Barrientos-Gutierrez; Alisha N Wade; Daniela Oliveira de Melo; Ana S Semeão de Souza; Bruno P Nunes; Arokiasamy Perianayagam; Maoyi Tian; Lijing L Yan; Arpita Ghosh; J Jaime Miranda (My University, 2022)
Multimorbidity is a complex challenge affecting individuals, families, caregivers, and health systems worldwide. The burden of multimorbidity is remarkable in low- and middle-income countries (LMICs) given the many existing challenges in these settings. Investigating multimorbidity in LMICs poses many challenges including the different conditions studied, and the restriction of data sources to relatively few countries, limiting comparability and representativeness. This has led to a paucity of evidence on multimorbidity prevalence and trends, disease clusters, and health outcomes, particularly longitudinal outcomes. In this paper, based on our experience of investigating multimorbidity in LMICs contexts, we discuss how the structure of the health system does not favor addressing multimorbidity, and how this is amplified by social and economic disparities and, more recently, by the COVID-19 pandemic. We argue that generating epidemiologic data around multimorbidity with similar methods and definition is essential to improve comparability, guide clinical decision-making and inform policies, research priorities, and local responses. We call for action on policy to refinance and prioritize primary care and integrated care as the center of multimorbidity.
Keywords: epidemiology; evidence-based; low- and middle-income countries; multimorbidity.